Effect of Housing First on violence-related traumatic brain injury in adults with experiences of homelessness and mental illness: findings from the At Home/Chez Soi randomised trial, Toronto site. Issue 12 (4th December 2020) - Mejia-Lancheros, Cilia; Lachaud, James; Stergiopoulos, Vicky; Matheson, Flora I.; Nisenbaum, Rosane; O'Campo, Patricia; Hwang, Stephen W.
Abstract : Objectives: People experiencing homelessness have a high prevalence and incidence of traumatic brain injury (TBI) due to violence. Little is known about the effectiveness of interventions to reduce TBI in this population. This study assessed the effect of Housing First (HF) on violence-related TBI in adults with experiences of homelessness and mental illness. Design: Pragmatic randomised trial. Participants: 381 participants in the Toronto site of the At Home/Chez randomised trial. Intervention: HF participants were provided with scattered-site housing using rent supplements and supports from assertive community treatment or intensive case management teams (n=218, 57.2%). Control participants had access to treatment as usual (TAU) in the community (n=163, 42.8%). Main outcome measures: Primary outcomes were an incident physical violence-related TBI event and the number of physical violence-related TBI events during the follow-up period (January 2014 to March 2017). Interval-censored survival time regression and zero-inflated negative binomial regression were used to assess the effect of HF on primary outcomes. Results: Among study participants, 9.2% (n=35) had an incident physical violence-related TBI event, and the mean physical violence-related TBI events was 0.16 (SD ±0.6). Compared with TAU participants, HF participants did not have a significantly lower risk of an incident violence-related TBI event (adjusted HR : 0.58 (95% CI, 0.29 to 1.14)), but they had a significantly lower number of physical violence-related TBI events (unadjusted incidence rate ratio (IRR): 0.22 (95% CI, 0.06 to 0.78); adjusted IRR: 0.15 (95% CI, 0.05 to 0.48)). Conclusion: HF may be a useful intervention to reduce the burden of TBI due to physical violence among homeless individuals with mental illness. Trial registration number: ISRCTN42520374 .